Quand le texte signale sa structure : la fonction textuelle des noms sous-spécifiés - Dominique Legallois (Corela)
“Linking sequences” are cohsive devices by which some texts are organised; for example, the well-kwnown problem-solution schema is a general principle that expains the semantic connection within as well as between the clauses of a text. These patterns are often signaled by a category of “unspecific nouns” which can take a nominalisation as complement in the construction “N-be-that ...” (idea, problem, solution, question, etc.). We illustrate in this paper the characteristics and functions of both “linking sequences” and “unspecific nouns”.